(untitled) (International Educators Conference, 2025)
Otitis externa is an infection that causes inflammation (redness and swelling) of the ear canal, which is the tube between the outer ear and the eardrum. Otitis externa is often called ‘swimmer’s ear’ because regularly getting water in your ear can make inflammation more likely. External otitis is an acute infection of the ear canal skin typically caused by bacteria; Pseudomonas is most common. Symptoms include pain, discharge, and hearing loss if the ear canal has swollen shut; manipulation of the auricle causes pain. Diagnosis is based on history and inspection. Treatment is with careful debridement of dead skin and wax, topical medications (including antibiotics, corticosteroids, and acetic acid or a combination), and dry ear precautions.